Novel and validated titrimetric method for determination of selected angiotensin-II-receptor antagonists in pharmaceutical preparations and its comparison with UV spectrophotometric determination - Shrikant H. Patil; Minakshi V. Janjale (Elsevier, 2012)
A novel and simple titrimetric method for determination of commonly used angiotensin-II-receptor antagonists (ARA-IIs) is developed and validated. The direct acid base titration of four ARA-IIs, namely eprosartan mesylate, irbesartan, telmisartan and valsartan, was carried out in the mixture of ethanol:water (1:1) as solvent using standardized sodium hydroxide aqueous solution as titrant, either visually using phenolphthalein as an indicator or potentiometrically using combined pH electrode. The method was found to be accurate and precise, having relative standard deviation of less than 2% for all ARA-IIs studied. Also, it was shown that the method could be successfully applied to the assay of commercial pharmaceuticals containing the above-mentioned ARA-IIs. The validity of the method was tested by the recovery studies of standard addition to pharmaceuticals and the results were found to be satisfactory. Results obtained by this method were found to be in good agreement with those obtained by UV spectrophotometric method. For UV spectrophotometric analysis ethanol was used as a solvent and wavelength of 233 nm, 246 nm, 296 nm, and 250 nm was selected for determination of eprosartan mesylate, irbesartan, telmisartan, and valsartan respectively. The proposed titrimetric method is simple, rapid, convenient and sufficiently precise for quality control purposes. Keywords: Angiotensin-II-receptor antagonists, Titrimetric assay, UV spectrophotometry, Validation